2008
DOI: 10.1172/jci31073
|View full text |Cite
|
Sign up to set email alerts
|

Central insulin action regulates peripheral glucose and fat metabolism in mice

Abstract: Insulin resistance is a hallmark of type 2 diabetes, and many insights into the functions of insulin have been gained through the study of mice lacking the IR. To gain a better understanding of the role of insulin action in the brain versus peripheral tissues, we created 2 mouse models with inducible IR inactivation, 1 in all tissues including brain (IR Δwb ), and 1 restricted to peripheral tissues (IR Δper ). While downregulation of IR expression resulted in severe hyperinsulinemia in both models, hyperglycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
213
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(233 citation statements)
references
References 70 publications
14
213
0
3
Order By: Relevance
“…This enhancement may occur mainly in the classical insulinsensitive tissues liver [6], adipocytes [7] and muscle [8], as suggested by animal studies.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This enhancement may occur mainly in the classical insulinsensitive tissues liver [6], adipocytes [7] and muscle [8], as suggested by animal studies.…”
Section: Discussionmentioning
confidence: 70%
“…Thus insulindependent hepatic glucose production [6], fat metabolism in adipocytes [7] and muscle glycogen synthesis [8] are all influenced by central actions of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Mice with brain insulin receptor inactivation had worse hyperglycemia and failed to increase hepatic STAT3 phosphorylation or up-regulate IL-6 expression. Furthermore, control mice given chronic ICV insulin had increased fat mass and adipose tissue lipoprotein lipase expression (30). This work highlights the importance of central insulin in regulating peripheral glucose and lipid metabolism via hepatic STAT3 activation.…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 62%
“…ICV insulin infusion also failed to increase hepatic STAT3 phosphorylation in mice lacking IL-6 (28), suggesting that central insulin may function via IL-6-mediated hepatic STAT3 activation to suppress EGP. The importance of hepatic STAT3 was further shown in mice with inducible insulin receptor inactivation, either in the whole body or in peripheral tissues only (30). Mice with brain insulin receptor inactivation had worse hyperglycemia and failed to increase hepatic STAT3 phosphorylation or up-regulate IL-6 expression.…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 97%
“…Whether leptin's actions on brain neurons can robustly improve hyperglycemia (and other metabolic imbalances) in the context of insulin deficiency has not been tested. Recently, however, exciting results have indicated that overt hyperglycemia and death caused by insulin signaling deficiency can be reversed by leptin therapy alone (25,26), thus suggesting that insulin is dispensable for the glycemia-lowering actions of leptin. Nevertheless, the mechanism(s) by which leptin monotherapy improves T1D is unknown.…”
mentioning
confidence: 99%